Traumatic Foreign Body into the Face: Case Report and Literature Review - Maysa Nogueira de Barros Melo; Lidyane Nunes Pantoja; Sara Juliana de Abreu de Vasconcellos; Viviane Almeida Sarmento; Christiano Sampaio Queiroz (Case Reports in Dentistry)
This paper describes a case of mouth opening limitation, secondary to a facial trauma by cutting-piercing instrument, whose fragments had not been diagnosed in the immediate posttrauma care. Description of an unusual surgical maneuver and a literature review are presented.